2012
DOI: 10.1111/j.1468-3083.2012.04599.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis as initiator or amplifier of the systemic inflammatory march: impact on development of severe vascular events and implications for treatment strategy

Abstract: Our results suggested that two scenarios of systemic inflammatory marches are present among psoriatic patients with metabolic disorder and judicious use of methotrexate may reduce the risk of cerebrovascular event, especially when psoriasis served as the disease amplifier of the systemic inflammatory march.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Sex was mainly linked to frequencies of hypertension and smoking, and the severity of psoriasis to obesity. A recent Taiwanese case–control study evaluated whether the sequence of events psoriasis and metabolic disorder onsets could affect the risk for subsequent development of cardiovascular complications . Psoriasis was considered the initiator of the inflammatory march when comorbidities developed after its onset, and was a potent amplifier of pre‐existing comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Sex was mainly linked to frequencies of hypertension and smoking, and the severity of psoriasis to obesity. A recent Taiwanese case–control study evaluated whether the sequence of events psoriasis and metabolic disorder onsets could affect the risk for subsequent development of cardiovascular complications . Psoriasis was considered the initiator of the inflammatory march when comorbidities developed after its onset, and was a potent amplifier of pre‐existing comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the risk of developing severe vascular events is higher when psoriasis acts as the disease amplifier compared to when it acts as the disease initiator. In addition, when psoriasis acts as the disease amplifier, methotrexate therapy was associated with a lower risk of developing cerebrovascular disease [ 50 ].…”
Section: Psoriasis and Severe Vascular Eventsmentioning
confidence: 99%
“…Epidemiology studies from different parts of the world have repeatedly shown that psoriasis is associated with higher occurrences of different components of metabolic syndrome and severe vascular complications [1]. Therefore, psoriasis is currently considered as a systemic inflammatory disorder and that the concept of ''psoriatic march'', with psoriasis serving as the initiator or the amplifier of the systemic inflammatory march, has been proposed to explain the increased occurrences of severe vascular events observed among psoriatic patients [3,4]. In terms of life expectancy, psoriatic patients were shown to have a higher mortality rates as compared to general population, particularly due to cardiovascular diseases and malignancies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%